Evaluating the Relationship between Overconfidence of Senior Managers and Abnormal Cash Fluctuations with respect to Financial Flexibility in Companies Listed in Tehran Stock Exchange - Hadi Mousavi,; Majid Davoudi Nasr, (Technium Social Sciences Journal, 2020)
Executives can maximize profits by recognizing the factors that effects investment and using them to obtain the optimal level of investment,) Inefficient markets have shortcomings that can impact the optimal level of investment leading to the process of over- investment or under- investment. In the present study, the relationship between overconfidence of senior managers and abnormal cash fluctuations with respect to financial flexibility in companies listed in Tehran stock exchange" from 2009 to 2013 were evaluated. In this study, the sample consists of 84 companies selected by systematic elimination method and 420 year-companies in total. In this research, EVIEWS software was used to test the research hypotheses by linear regression and correlation coefficient and after designing and testing the research hypothesis. After designing and testing research hypotheses that have been used to each hypothesis, it was concluded that there was a significant relationship between overconfidence of senior managers and abnormal cash fluctuations , and this relationship was not significant at any level of financial flexibility. Moreover, the findings of research showed that there was a significant relationship between senior manager’s overconfidence and positive abnormal cash flow fluctuations in firm and this relationship is significant only at the level of companies with high financial flexibility. Finally, the results indicate that there is no significant relationship between senior managers 'overconfidence and negative cash flow abnormalities, and the relationship between senior managers' overconfidence and negative cash flow fluctuations at the level of companies with high financial flexibility was confirmed.